What we can learn from mismatched and unexpected responses to questions in interviews with people who have traumatic brain injury. (3rd July 2017) - Davis, Boyd; Maclagan, Margaret; Ferguson, Pamela; Pope, Charlene; Olsen, Jama; Fakhry, Samir
Abstract : This article analyses mismatched and unexpected responses to questions in a survey administered to thirteen people with traumatic brain injury or their relatives. Rather than giving simple one word or yes-no answers, the respondents provided unexpected narrative answers that went beyond the scope of the survey questions. The analysis identifies the types of narratives used by the respondents and highlights the ways in which they expressed their concerns about their life post-injury. It ends with a plea for more information to be provided to patients and their relatives about the 'new normal' life after a traumatic brain injury.